2018
DOI: 10.3390/en11040723
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Health Status of Wind Turbines by Using Self Organizing Maps and Interpretation-Oriented Post-Processing Tools

Abstract: Background: Identifying the health status of wind turbines becomes critical to reduce the impact of failures on generation costs (between 25-35%). This is a time-consuming task since a human expert has to explore turbines individually. Methods: To optimize this process, we present a strategy based on Self Organizing Maps, clustering and a further grouping of turbines based on the centroids of their SOM clusters, generating groups of turbines that have similar behavior for subsystem failure. The human expert ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…To determine the origin, they compute a statistic of which variable has had the greatest contribution to generate the distance from the BMU. Following with the SOM techniques, authors such as Blanco-M. et al [39] propose a process that includes a clustering technique on the result of the turbines after applying SOM, in order to identify the health status of the turbines. Other authors, such as Leahy et al [40], focus on clustering groups of alarms, detecting particular sequences before a failure.…”
Section: Introductionmentioning
confidence: 99%
“…To determine the origin, they compute a statistic of which variable has had the greatest contribution to generate the distance from the BMU. Following with the SOM techniques, authors such as Blanco-M. et al [39] propose a process that includes a clustering technique on the result of the turbines after applying SOM, in order to identify the health status of the turbines. Other authors, such as Leahy et al [40], focus on clustering groups of alarms, detecting particular sequences before a failure.…”
Section: Introductionmentioning
confidence: 99%
“…Data Science (DS) is an emergent research field that helps better understand the complex mechanisms behind environmental phenomena. In Gibert et al (2018) an overview of what can be called the field of Environmental Data Science is provided. The paper describes the DS process, and the role of Data Mining (DM) methods, which is identified as one of the most critical to transform data into added value and new knowledge for ESs.…”
Section: Introductionmentioning
confidence: 99%
“…In Gibert et al (2018), the main challenges of Environmental Data Science are identified and discussed to promote research in the area. One of these main challenges is the lack of guidance in choosing the right analytics method for a given problem.…”
Section: Introductionmentioning
confidence: 99%
“…They suggest using cumulative particle counts to better detect failures instead of direct particle creation measurements and to combine various sensors in order to improve confidence in the diagnosis. In the work by the authors of [23], they create a health indicator based on the centroids proposed by a Self Organising Map in order to group WTs according to health status using SCADA data. This way operators are given additional information regarding the health state of the WTs, and can plan consequently.…”
mentioning
confidence: 99%